1998
DOI: 10.1002/1529-0131(199810)41:10<1867::aid-art20>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen replacement therapy and worsening of radiographic knee osteoarthritis: The Framingham study

Abstract: Objective. To examine whether estrogen replacement therapy (ERT) prevents worsening of radiographic knee osteoarthritis (OA) in elderly women.Methods. A total of 551 women ages 63-91 years (mean age 71) in the Framingham Study were followed up from biennial examination 18 (1983)(1984)(1985) to examination 22 (1992)(1993). Data on postmenopausal ERT were obtained every 2 years. Subjects were classified into 3 groups according to their estrogen use at biennial examination 18: never users (n = 349), past users (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(62 citation statements)
references
References 20 publications
2
58
0
2
Order By: Relevance
“…Accordingly, estrogen deficiency occurring with menopause has been associated with an increased incidence and severity of OA in women [39]. Postmenopausal women taking estrogen replacement therapy exhibit a reduced risk of hip and knee OA, compared with those not taking it [40,41]. …”
Section: Factors Affecting Subchondral Bone Integritymentioning
confidence: 99%
“…Accordingly, estrogen deficiency occurring with menopause has been associated with an increased incidence and severity of OA in women [39]. Postmenopausal women taking estrogen replacement therapy exhibit a reduced risk of hip and knee OA, compared with those not taking it [40,41]. …”
Section: Factors Affecting Subchondral Bone Integritymentioning
confidence: 99%
“…Unlike observational clinical studies, some radiographic studies have suggested a protective effect of ERT on the radiographic detection of OA or its progression [111-115]. In a cross-sectional study, ERT significantly reduced the risk of radiographic hip OA, particularly in long-term users [111].…”
Section: The Effects Of Estrogen Replacement Therapy and Selective Esmentioning
confidence: 99%
“…Similarly, an initial cross-sectional analysis of two of the largest studies found an inverse association between ERT use and radiological knee OA, suggesting that ERT may have a chondroprotective effect. However, a subsequent follow-up analysis failed to show significant ERT protection against either the development or progression of radiographic knee OA [112-115]. Additionally, contradictory results were described regarding the association between ERT and the requirement for arthroplasty [116].…”
Section: The Effects Of Estrogen Replacement Therapy and Selective Esmentioning
confidence: 99%
“…Approximately 25% of women developed arthralgia within 3 weeks of initiation of leuprolide. Alternatively, estrogen-based therapy is associated with reduced incidence of radiologic knee osteoarthritis and decreased incidence of joint pain/swelling [70-72]. However, this effect has not been seen in all studies of estrogen therapy [73].…”
Section: Etiology Of Aromatase Inhibitor-induced Arthralgiasmentioning
confidence: 99%